1997
DOI: 10.1038/nsb1197-953
|View full text |Cite|
|
Sign up to set email alerts
|

Structure of the profilin-poly-L-proline complex involved in morphogenesis and cytoskeletal regulation

Abstract: Profilin, a ubiquitous low molecular weight (13,000-15,000 M(r)) actin binding protein, regulates the formation of F-actin structures in vivo, and is localized to specific cellular regions through interaction with proline-rich sequences. Here we report the 2.2 A X-ray structure of the complex between human platelet profilin (HPP) and a decamer of L-proline (L-Pro10). The L-Pro10 peptide adopts a left-handed type II poly-L-proline helix (PPII) and binds to a highly conserved patch of aromatic amino acids on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
148
0
6

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(167 citation statements)
references
References 49 publications
12
148
0
6
Order By: Relevance
“…In recent years, the left-handed polyproline II (PPII) 1 helical conformation has been elevated from the status of a relatively rare and seemingly uninteresting secondary structure to one that is surprisingly common and of the utmost importance. This structure plays a central role in numerous vital processes including signal transduction, transcription, cell motility, and the immune response.…”
mentioning
confidence: 99%
“…In recent years, the left-handed polyproline II (PPII) 1 helical conformation has been elevated from the status of a relatively rare and seemingly uninteresting secondary structure to one that is surprisingly common and of the utmost importance. This structure plays a central role in numerous vital processes including signal transduction, transcription, cell motility, and the immune response.…”
mentioning
confidence: 99%
“…Whereas all of the maize pollen profilin isoforms have K d values of ‫572ف‬ M proline residues (Gibbon et al, 1997), ZmPRO4 has a substantially higher affinity, with a K d of 173 M proline residues. Eight of the most highly conserved residues in eukaryotic profilins ( Thorn et al, 1997), marked with asterisks in Figure 1, have been implicated in PLP binding by using mutagenesis (Björkegren et al, 1993;Haarer et al, 1993), nuclear magnetic resonance spectroscopy (Metzler et al, 1994; Domke et al, 1997), and x-ray crystallography (Mahoney et al, 1997). The hydroxyl group of tyrosine-6 was shown to interact directly with the backbone of the PLP peptide (Mahoney et al, 1997), and the Y6F mutation in human profilin I was shown to elute from PLP-agarose at a lower concentration of urea than did the wild-type protein (Sohn et al, 1995).…”
mentioning
confidence: 99%
“…Many more intracellular and extracellular modular protein domains have been identi®ed (reviewed by Bork et al, 1997). However, their ligands are as yet unknown, and signi®cant portions of the newly described modules so far seem to be con®ned to a limited number of specialized proteins that this domain will also bind its proline-rich ligand in a way in which individual proline residues contact the domain directly as well as serve a sca olding function to maintain the polyproline II helical structure, as was documented for ligands to SH3, WW and pro®lin (Yu et al, 1994;Macias et al, 1996;Mahoney et al, 1997).…”
Section: Degeneracy In The`protein Recognition Code'mentioning
confidence: 99%
“…Ligands for certain SH3 domains and ligands for group II WW domains, share a PPLP core (Sudol, 1996b). In addition, many physiological binders of pro®lin, including Mena, VASP, cdc12p, p140m Dia and Cappucino, all contain long runs of prolines interrupted or terminated by leucine (Mahoney et al, 1997). It is the PPLP core(s) of Mena that interact(s) with the WW domain of the FE65 adapter protein linked to the Alzheimer's beta amyloid precursor (Ermekova et al, 1997).…”
Section: Degeneracy In The`protein Recognition Code'mentioning
confidence: 99%
See 1 more Smart Citation